2012
DOI: 10.1029/2012jd018246
|View full text |Cite
|
Sign up to set email alerts
|

The spatiotemporal variability of lightning activity in the Himalayan foothills

Abstract: [1] The spatiotemporal variability of lightning activity in the region of the Himalayan foothills and perpendicular to it has been examined from about 16-year data from the TRMM satellite. The monthly mean flash rate for the period from 1995 to 2010 is maximum in an arc-shaped area along the Himalayan foothills and decreases on both the north and south sides of it. Seasonal variation of mean flash rate changes from annual to semiannual as the area shifts from north to south of the Himalayas and the average ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 34 publications
4
29
0
Order By: Relevance
“…Such accumulations of ice particles have also been reported to be positively correlated with CAPE and the updraft speed Rutledge et al, 1992;Zipser, 1994;Petersen et al, 1996]. Our results of the empirical orthogonal function (EOF) analysis show that 22% changes in flash rate in the Himalayan foothills can be associated with variability in CAPE [Penki and Kamra, 2012a].…”
Section: Introductionsupporting
confidence: 51%
See 1 more Smart Citation
“…Such accumulations of ice particles have also been reported to be positively correlated with CAPE and the updraft speed Rutledge et al, 1992;Zipser, 1994;Petersen et al, 1996]. Our results of the empirical orthogonal function (EOF) analysis show that 22% changes in flash rate in the Himalayan foothills can be associated with variability in CAPE [Penki and Kamra, 2012a].…”
Section: Introductionsupporting
confidence: 51%
“…In the tropics, lightning responds sensitively to surface temperature at many sites [Williams, 1992], and flash rate tends to be maximum at the time of peak cloud height [Frost, 1954;Williams, 1991]. Recent study of Penki and Kamra [2012a] shows that lightning flash rate is highly correlated with surface temperature in the Himalayan foothills of the northwestern India. This association in specific locations and meteorological regimes is attributed to the gravitational energy of large ice particles in the upper regions of the storm.…”
Section: Introductionmentioning
confidence: 99%
“…Deep convection may result into towering clouds up to the tropopause leading to the possibility of enhanced lightning activity. However, CAPE is not the sole parameter to control lightning activity as is evident from the fact that for the same value of CAPE over land surface and warm ocean water, maritime lightning activity is much reduced (Lucas et al, 1994;Kandalgaonkar et al, 2005;Tinmaker et al, 2010;Kumar and Kamra, 2012;Siingh et al, 2015). One of the reasons may be difference in conversion efficiency of CAPE to updraft kinetic energy.…”
Section: Convection Cape and Lightningmentioning
confidence: 91%
“…This suggests that surface properties are not the only cause of difference in convective processes over continents and oceans. Kumar and Kamra (2012) considered three sea regions (Arabian Sea (AS), Bay of Bengal (BB) and Chinese Sea (CS)) and two land regions (the Peninsular India (PI) and Indo-China Peninsula (ICP)) and showed that the flash rates over peninsular region (PI and ICP) are 2.6-33 times of those over sea regions (AS, BB, CS). The flashes occurring over oceans are more energetic than those occurring over peninsulas.…”
Section: Convection Over Land and Ocean Surfaces And Lightningmentioning
confidence: 99%
“…We do not identify diamond because our quench rates are too high, however, we do synthesise concentric shell fullerenes that may serve as nanoscopic pressure cells to vapour-deposited (CVD) diamonds (Banhart and Ayajan, 1996;Sorkin et al, 2011). The Luobusa ophiolite in Tibet where the unusual mineral assemblages are documented in most detail is situated at an altitude in excess of 4000 m, in a region where lightning strikes are frequent (Kumar and Kamra, 2012). The lithologies in which UHP and ultra-reduced minerals are found -serpentinised harzburgite and podiform chromitite -are electrically highly conductive lithologies and prone to attract lightning strikes.…”
Section: Introductionmentioning
confidence: 99%